Forced Convection of MHD Radiative Jeffrey Nanofluid Over a Moving Plate - Syazwani, Mohd Zokri; Nur Syamilah, Arifin; Abdul Rahman, Mohd Kasim; Norhaslinda, Zullpakkal; Mohd Zuki, Salleh (Akademi Baru, 2021)
Convectively heated Jeffrey nanofluid flow in the presence of magnetic field and thermal radiation is investigated from a moving plate. Parameter of Brownian motion from Boungiorno model is the imperative mechanism that contributes to the heat transfer enhancement. Governing equations, consisting of the continuity, momentum, energy and nanoparticle concentrations equations are transformed into dimensionless form by means of the appropriate similarity transformation variables. Numerical results via Runge-Kutta Fehlberg Fourth-Fifth order (RKF45) method are specifically acquired on the impact of physical parameters such as Brownian motion, magnetic parameter, ratio of relaxation to retardation and radiation parameters over the temperature and nanoparticles concentration profiles. Comparison of the present results with existing published studies has validated the accuracy of the numerical solutions. Graphical representation of different magnetic parameters has caused the increment in both temperature and nanoparticles concentration profiles. On the other hand, enhancement of Brownian motion has intensified the temperature but declined the nanoparticles concentration.